2004
DOI: 10.3141/1891-05
|View full text |Cite
|
Sign up to set email alerts
|

Field and Laboratory Investigation of Permeable Asphalt Mixes on Georgia Highways

Abstract: The Georgia Department of Transportation (GDOT) investigated possible high permeability in asphalt mixes statewide in response to reports of prolonged wetness on pavements around the state after rainfall. In these locations, high permeability manifested itself as wet areas on pavement surfaces where wetness remained after natural conditions should have removed all moisture from the surfaces. Sixteen project sites were inspected for problem areas statewide, and core specimens were taken from six of the sites. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In this section the ability of the calibrated equation to predict the permeability of a set of data that was not included in the calibration process is examined. A recent study by the Georgia Department of Transportation (GDOT) investigated the possible reasons for the high permeability of several highways in the state (26). Engineers obtained field cores from different highways and measured the permeability of these cores.…”
Section: Laboratory Permeability Measurementsmentioning
confidence: 99%
“…In this section the ability of the calibrated equation to predict the permeability of a set of data that was not included in the calibration process is examined. A recent study by the Georgia Department of Transportation (GDOT) investigated the possible reasons for the high permeability of several highways in the state (26). Engineers obtained field cores from different highways and measured the permeability of these cores.…”
Section: Laboratory Permeability Measurementsmentioning
confidence: 99%
“…In recent years, numerous research works have been performed in a number of states in an attempt to study the permeability characteristic and ultimately recommend a reliable test method or acceptance permeability criteria (Choubane et al 1998;Maupin 2000;Cooley et al 2001;Mogawer et al 2002;Brandon et al 2004;Owusu-Ababio and Schmitt 2009;Tarefder and Ahmad 2015). Other studies have attempted to propose permeability limits to be added to the current quality assurance (QA) and quality control (QC) (Williams et al 2009;Williams, 2011;Chen et al 2013).…”
mentioning
confidence: 99%
“…The common laboratory method that is adopted to measure the coefficient of permeability for HMA cores or laboratory prepared specimens was developed by the Florida Department of Transportation (FDOT) in 1996 [James, et al, 2004] This test method ( Figure 2.13) has been selected as the standard lab test for measuring permeability and the procedure is outlined in ASTM PS 129-01, Permeability of Bituminous Materials [Zaniewski and Yan, 2013]. The method follows the falling head principle to measure the coefficient of permeability.…”
Section: 53a Karol-warner Asphalt Permeametermentioning
confidence: 99%
“…and Oklahoma in an attempt to establish testing methods for measuring the initial permeability as a quality indicator of newly paved highways and develop acceptance criteria limits [Tarefder and Ahmed, 2014;Mogawer, et al, 2002;Maupin, 2000a] [Choubane, 1998;Owusu-Ababio and Schmitt, 2009]. Studies have shown that the coefficient of permeability is an important pavement property that can be used as an indicator for the pavement's performance over time [James, et al, 2004;Maupin, 2000a;Cooley, et al, 2001].…”
Section: Introductionmentioning
confidence: 99%